EVALUATION OF CONCRETE CONSTRUCTION COLLAPSE ON THE MARTAPURA RIVERBANK AND SAFE DESIGN - Rindhani, Nadia Afiqah; Rusdiansyah, Rusdiansyah (CERUCUK, 2025)
The footbridge in Gang Gusti Galuh is a construction built for the needs of local pedestrian traffic, over time the footbridge collapsed. The collapse of the Concrete Footbridge Construction in Gang Gusti Galuh in early 2024 between January-February has added to the series of concrete construction failures in Indonesia, especially in South Kalimantan.The collapse of this bridge was due to inadequate foundation support and the influence of inhomogeneous soil. The purpose of this design is to determine the cause of the collapse and analyze what forces occur in the construction and its new design that is safe to use. The results of this evaluation indicate that the existing condition of the bridge with a wooden foundation is not safe to use and will be replaced with a new foundation using concrete piles to be more adequate and safe to use. Keywords: Construction, Footbridge, Redesign